2012
DOI: 10.1258/ar.2012.110562
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between benign and malignant breast tumors using kinetic features of real-time harmonic contrast-enhanced ultrasound

Abstract: Background Contrast-enhanced ultrasound (CEUS) has gained interest because of its ability to gather vascular information in diverse organs. There is still a subject of debate concerning its value in breast lesions, especially as a differential diagnostic tool. Purpose To investigate whether kinetic parameters of CEUS can differentiate between malignant and benign breast lesions. Material and Methods We evaluated 75 malignant and 21 benign lesions in the breast or axilla. Contrast harmonic imaging (CHI) US was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 34 publications
(40 reference statements)
1
45
0
Order By: Relevance
“…Saracco et al analysed the enhancement kinetics of 96 breast tumours. They found that signal drop from peak to the intensity measured at 50 s was significantly greater in malignant tumours compared to benign lesions [15]. The pathophysiology behind the two observed morphological wash-out patterns remains speculative.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Saracco et al analysed the enhancement kinetics of 96 breast tumours. They found that signal drop from peak to the intensity measured at 50 s was significantly greater in malignant tumours compared to benign lesions [15]. The pathophysiology behind the two observed morphological wash-out patterns remains speculative.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, with the implementation of high-frequency probes, the spatial resolution of contrast imaging is significantly improved; thus, a greater number of details can be acquired for morphological assessment. Although several studies show that CEUS detects breast tumours [14][15][16], to the best of our knowledge, the enhancement features of papillary lesions have not yet been reported. Further, there is little information regarding the comparison of these breast abnormalities with other benign lesions that mimic papillary lesions.…”
Section: Introductionmentioning
confidence: 87%
“…Various quantitative parameters were significant for differentiating between malignant and benign lesions in kinetic curve analysis using dynamic contrast-enhanced breast magnetic resonance imaging, including wash-out ratio. [16][17][18][19] However, only 1 previous report 14 suggested that Receiver operating characteristic curve analysis of a 15-mm circular ROI for the peak signal intensity, time to peak, and initial slope showing diagnostic accuracy in differentiation between benign and malignant breast lesions. Abbreviations are as in Table 1. the wash-out ratio was significant on contrast-enhanced breast sonography.…”
Section: Nakata Et Al-quantitative Analysis Of Contrast-enhanced Breamentioning
confidence: 99%
“…However, the methods of ROI selection varied between studies, and previous reports have not discussed appropriate ROI selection. [10][11][12][13][14] This study was performed to investigate whether there are significant differences in kinetic parameters between benign and malignant breast lesions using different ROIs based on raw data from the same contrast-enhanced breast sonographic examinations. To our knowledge, this study is the first quantitative analysis of breast contrast-enhanced sonography using the perflubutane-based contrast agent Sonazoid, and the results were compared with previous quantitative studies using another second-generation contrast agent (SonoVue).…”
mentioning
confidence: 99%
“…Liver and breast lesions can be characterized by tumor vasculature and perfusion, which are visualized with perflubutane (Hatanaka et al 2008;Luo et al 2009;Miyamoto et al 2012Miyamoto et al , 2014 as well as with other micro-bubbles (Berry and Sidhu 2006;Saracco et al 2012). As the microbubbles distribute in the micro-circulation of the whole body (Toft et al 2006), it is expected that they will be applicable for imaging tumors in other organs and is known to be stable enough in vivo for the duration of the ultrasound examination (Marelli 2000).…”
mentioning
confidence: 99%